A controlled trial of artemether or quinine in Vietnamese adults with severe falciparum malaria. - Tran, T; Day, N; Nguyen, H; Nguyen, T; Tran, T; Pham, P; Dinh, X; Ly, VC; Ha, V; Waller, D; Peto, T; White, N (1996)
BACKGROUND: Artemisinin (qinghaosu) and its derivatives are rapidly effective antimalarial drugs derived from a Chinese plant. Preliminary studies suggest that these drugs may be more effective than quinine in the treatment of severe malaria. We studied artemether in Vietnam, where Plasmodium falciparum has reduced sensitivity to quinine. METHODS: We conducted a randomized, double-blind trial in 560 adults with severe falciparum malaria. Two hundred seventy-six received intramuscular quinine dihydrochloride (20 mg per kilogram of body weight followed by 10 mg per kilogram every eight hours), and 284 received intramuscular artemether (4 mg per kilogram followed by 2 mg per kilogram every eight hours). Both drugs were given for a minimum of 72 hours. RESULTS: There were 36 deaths in the artemether group (13 percent) and 47 in the quinine group (17 percent; P = 0.16; relative risk of death in the patients given artemether, 0.74; 95 percent confidence interval, 0.5 to 1.11). The parasites were cleared more quickly from the blood in the artemether group (mean, 72 vs. 90 hours; P < 0.001); however, in this group fever resolved more slowly (127 vs. 90 hours, P < 0.001), the time to recovery from coma was longer (66 vs. 48 hours, P = 0.003), and the hospitalization was longer (288 vs. 240 hours, P = 0.005). Quinine treatment was associated with a higher risk of hypoglycemia (relative risk, 2.7; 95 percent confidence interval, 1.7 to 4.4; P < 0.001), but there were no other serious side effects in either group. CONCLUSIONS: Artemether is a satisfactory alternative to quinine for the treatment of severe malaria in adults.